Study of Safety of Potash As A Food Additive - Onuigbo Hyginus Ndubisi (Sokoto Journal of Medical Laboratory Science)
Potash is an organic substance used by many communities of the world for different purposes. However, its safety has been very uncertain before now limiting its use by many communities to achieve their desired culinary. We, therefore, conducted toxicological parity animal study to ascertain safety of this condiment in food preparations to clear the paranoid associated with its use.  Pure commercial potash was used to carry out lethal dose (LD 50) test for acute toxicity on 12 healthy male Wistar rats in 2 phases. This was followed by parity biochemical investigations on liver, albumin, serum electrolytes and kidney profiles of 30 healthy male grouped Wistar rats after feeding the rats on different graded doses of potash in pure highly profiled commercial feed for 28 days for chronic toxicity. The highest dose of 500mg/kg body weight of potash was tolerated by the study animals and, therefore, there was no morbidity or mortality. The biochemical parameters investigated including liver enzymes (ALT, AST, ALP); Albumin; Serum Electrolytes (NA+, K+, CL-, HCO3-) and Kidney functions (Urea and Creatinine) were within established normal ranges of the parameters. The values obtained from the test groups of the animals did not deviate significantly from the values of the parity control study group (p<0.05). Potash, which is used for different purposes at a minimal dose has no deleterious effects on our study animals.